Cable area distribution in cable stayed bridges - Singh P.K. (My University, 2025)
Maximum cable stresses in a cable-stayed bridge having equal cable area, under live load condition, vary considerably. From design point of view, it is preferable to distribute the total cable area among different cables in such a way that under dead load and pre-tension condition with worst live load placements on the girder, the maximum cable stresses in different cables become equal. A simple iterative approach by modifying cable areas in proportion to their maximum stresses is presented in this paper. It is found that the convergence leads to equal maximum cable stress condition with lower maximum stress level as well as lower stress amplitudes. The girder and tower moments and deflections are also found to decrease for such a solution indicating further suitability of the method.